ANALYSIS OF ACCOUNTABILITY AND TRANSPARENCY IN FINANCIAL MANAGEMENT VILLAGE OWNED ENTERPRISES (BUMDES) TINARANGEN NIAMPAK, BEO SELATAN DISTRICT, TALAUD ISLANDS DISTRICT - Elistriani Taengetan; Hendrik Manossoh; Victorina Tirayoh (ACCOUNTABILITY, 2022)
Village-Owned Enterprises (BUMDes) as public agencies in a community service organization, are required to apply the principles of accountability and transparency as good governance in public service organizations. This study aims to determine the accountability and transparency of the financial management of BUMDes Tinarangen Niampak, Beo Selatan District, Talaud Islands Regency. The research method used is descriptive qualitative. The types of data used are qualitative data and quantitative data. data sources used are primary data and secondary data. Data collection techniques used in this study were observation, interviews and documentation. The informants in this study were the Head of Niampak Village, Supervisor of BUMDes Tinarangen, Chairman, Secretary and Treasurer of BUMDes Tinarangen, as well as the community who were customers and not customers of BUMDes Tinarangen. The results of the study show that (1) Accountability in the financial management of Tinarangen BUMDes is not optimal, because there are weaknesses in the implementation, administration, reporting and accountability stages. (2) Transparency in the financial management of BUMDes Tinarangen has not been optimal, because there is no access that makes it easy for the public to obtain information about the financial.